Labor Training and Foreign Direct Investment. Issue 1 (February 2014) - Liu, Qing; Qiu, Larry D.
Abstract Evidence shows that most foreign direct investment (FDI) flows from developed to developed countries (North–North) in skilled labor‐intensive industries. This paper builds a model that incorporates labor training into the proximity–concentration tradeoffs to analyze the entry mode of multinationals to a foreign country. Production requires both skilled labor and unskilled labor.. A multinational pursuing FDI needs to provide training to some workers in the host country to equip them with skills that are specific to the production of the firm. Labor training and skill specificity lead to contract friction. It is shown that in skilled labor‐intensive industries, FDI increases along with the economic development level of the host country, whereas in unskilled labor‐intensive industries, the reverse is true. This paper provides a theoretical explanation for the empirical findings on the prevalence of North–North FDI in skilled labor‐industries and North–South FDI in unskilled labor‐intensive industries.